Unveiling Earning Management Practices: A Qualitative Analysis of Accounting Research - Nasrun, Muhammad; Adil, Muhammad (Atestasi : Jurnal Ilmiah Akuntansi, 2024)
This research explores earning management practices through a qualitative analysis of accounting literature. It aims to elucidate the motives, mechanisms, and consequences of earning management, considering diverse industry contexts and regulatory environments. The study utilizes a comprehensive review of empirical studies, industry-specific research, and regulatory interventions to uncover nuanced patterns and emerging trends in earning management behavior. Findings indicate that earning management practices vary across industries, with regulated sectors exhibiting higher manipulation levels. Competitive dynamics also influence earning management decisions, with firms in fiercely competitive environments more likely to engage in aggressive tactics. Regulatory interventions, notably the Sarbanes-Oxley Act of 2002, have played a crucial role in deterring opportunistic practices. Despite regulatory efforts, challenges persist, including adaptive responses and unintended consequences such as regulatory arbitrage and greenwashing. The study underscores the importance of contextual factors in shaping earning management practices and highlights the need for tailored regulatory interventions and governance mechanisms. The research contributes to theoretical advancement in accounting, finance, and corporate governance and provides managerial insights into navigating ethical dilemmas and upholding transparency and integrity in financial reporting.